A Sinus Venosus Atrial Septal Defect Is Diagnosed by Echocardiography with an Unusual Bubble Study. Issue 6 (1st April 2013) - Dorosz, Jennifer L.; Fonseca, Brian M.; Kay, Joseph D.; Graham, Brian B.; Salcedo, Ernesto E.; Quaife, Robert A.
Mini‐Abstract A 68‐year‐old man underwent echocardiogram with agitated saline for a presumed diagnosis of primary pulmonary hypertension. Surprisingly, the bubbles from the agitated saline enter the left heart before filling the right side, leading to a diagnosis of Eisenmeger's syndrome from a sinus venosus atrial septal defect. Because of high right‐sided pressure, the bubbles preferentially travel from the superior vena cava through the defect to the right superior pulmonary vein and left atrium, rather than the right side. This diagnosis was later confirmed on cardiac MRI.